High-Dose Fish Oil Supplementation Increase Tacrolimus Exposure in Stable Renal Transplant Recipients. (July 2018) - Robertsen, Ida; Åsberg, Anders; Midtvedt, Karsten; Vethe, Nils Tore; Hartmann, Anders; Størset, Elisabet; Jenssen, Trond; Svensson, My Hanna Sofia; Eide, Ivar Anders
Abstract : Introduction: Development of cardiovascular (CV) disease due to unwanted side effects of immunosuppression is common following renal transplantation. Tacrolimus (Tac) is known to have negative impact on CV risk factors. In this setting, high-dose fish oil supplementation may have beneficial effects on both renal function and CV risk profile. However, it is not known if administration of fish oil affects Tac concentrations. The aim of the present study was to investigate the potential effects of fish oil on once-daily Tac pharmacokinetics in renal transplant recipients. Methods: A single center prospective study was conducted. Fifteen stable renal transplant recipients receiving once-daily tacrolimus (Advagraf®), mycophenolate and a steroid-based immunosuppression were included in the study. Two 8-hr pharmacokinetic investigations were performed before and after 4 weeks of fish oil administration (2.55 g/day). Tac dosing remained unchanged during the treatment period. Standard non-compartmental methods were used to determine pharmacokinetic parameters and the European Medicines Agency guidelines for bioequivalence studies to assess the possible pharmacokinetic interaction. Results: Twelve patients, median age 59 years (range 28-75) provided 2 evaluable pharmacokinetic Tac profiles. Concomitant administration of fish oil induced a 25 ± 30% increase in tacrolimus AUC0-8 ( P < 0.01). The bioequivalence criteria were not fulfilled; the mean before:after AUC0-8 and Cmax ratios were 1.22 (90% CI: 1.08-1.37) and 1.20 (90% CI: 1.11-1.30), respectively. Tac trough concentrations also tended to increase from 5.5 ± 1.2 μg/L before to 6.3 ± 1.8 μg/L after administration of fish oil ( P =0.19). Conclusions: In renal transplant recipients, fish oil administration significantly increased the exposure of once-daily Tac. It is therefore advisable and warranted to closely monitor Tac concentrations following initiation and discontinuation of high-dose fish oil supplementation.